Web-Based Price Estimation and Data Entry Application in Pawnshops: Case Study on One of The Private Pawnshop Companies in Bandung - Rio Febrian; Rohmat Nur Ibrahim (P3M, STIE Pasundan, Bandung, Indonesia., 2023)
This study introduces a web-based application that has been developed to offer price estimation services and facilitate data input within pawnshop establishments. The primary objective of this program is to optimize the effectiveness of collateral evaluation procedures and streamline data entry for pawnshop personnel. The application's development methodology integrates web technology and advanced data management systems to enhance the accuracy and efficiency of price evaluation. The application's users will be able to access it via the web-based platform, where they may input pertinent collateral information. Subsequently, they will receive prompt and precise price estimates. The experimental findings suggest that this application can enhance productivity and mitigate the risk of human errors in the pricing calculation procedure. In addition, the web interface's user-friendly design enhances the application's ease of adoption among pawnshop officers. This application is anticipated to streamline customer care procedures and improve overall customer satisfaction within the pawnshop establishment.